Health profiles of foreign-born elderly women with HIV in Italy - Arsuffi, Stefania; Quiros-Roldan, Eugenia; Colombo, Fabio Riccardo; Fioretti, Benedetta; Candela, Caterina; Celesia, Benedetto Maurizio; Ferrara, Micol; Milic, Jovana; De Socio, Giuseppe Vittorio; Madeddu, Giordano; Cattelan, Anna Maria; Piconi, Stefania; et al. (Frontiers in Aging, 2025)
BackgroundAgeing trajectories for foreign-born individuals and women living with HIV remain poorly defined globally. This study aimed to characterize foreign-born women living with HIV aged ≥65 years (FWLH) and compare them to age-matched Italian women (IWLH) and foreign-born men living with HIV (FMLH).MethodsData were drawn from the multicenter Italian geriatric HIV cohort (GEPPO). We described sociodemographic characteristics, viro-immunological status, comorbidities, and multidimensional geriatric assessment in FWLH. A complete case analysis was supplemented by multiple imputation using the mice package with the Predictive Mean Matching (PMM) method, and pooled estimates were derived from regression models, that included an interaction term for sex × birthplace.ResultsWe included 330 participants: 285 (86.5%) women, 15 (4.5%) FWLH and 30 (9%) FMLH. Comparing FWLH to IWLH, lower CD4+/CD8+ ratio (beta −0.38; 95% confidence interval (CI) −0.79, 0.03; p-value = 0.069) and percentage of CD4+ cell (beta −10; 95% CI -16, −4.1; p-value = 0.001) and higher weight (beta 11; 95% CI 3.4, 18; p-value = 0.004) and BMI (beta 3.8; 95% CI 0.57, 7.0; p-value = 0.021) were observed. Comparing FMLH to FWLH, we found lower prevalence of multimorbidity (IRR 0.60, 95% CI 0.37, 0.98, p-value = 0.039) and osteoporosis, though risk difference for osteoporosis was not significant. In the interaction model, FWLH had a lower percentage of CD4+ cells (β = −0.38; 95% CI: −0.73, −0.02; p = 0.036).ConclusionFWLH in a geriatric cohort showed a profile of immune imbalance and higher weight, BMI, and multimorbidity; this may be possibly related to a worse metabolic profile and poorer access to care. However, there was no difference in virological response and antiretroviral therapies. Enhancing our understanding of older FWLH is crucial for promoting person-centered care a patient-centred care and healthy ageing in this population.